2014
DOI: 10.1007/s11033-014-3553-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of pH sensitive insulin-loaded nano hydrogels and evaluation of insulin releasing in different pH conditions

Abstract: In the recent years, temperature and pH-sensitive hydrogels were developed as suitable carriers for drug delivery. In this study, four different pH-sensitive nanohydrogels were designed for an oral insulin delivery modeling. NIPAAm-MAA-HEM copolymers were synthesized by radical chain reaction with 80:8:12 ratios respectively. Reactions were carried out in four conditions including 1,4-dioxan and water as two distinct solution under nitrogen gas-flow. The copolymers were characterized with FT-IR, SEM and TEM. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Samples analyzed from the nanogels in both PBS and HCl solutions showed that insulin release from nanogels was high in pH 6.8, and low in acidic environments. Thus, pH responsive insulin loaded nanogels can be considered as a potential candidate for oral insulin therapy [71]. Interpenetrating polymeric nanogels were prepared using biocompatible gelatin macromolecules and poly (acrylamidoglycolic) acid using free radical emulsion polymerization technique.…”
Section: Microgelsmentioning
confidence: 99%
“…Samples analyzed from the nanogels in both PBS and HCl solutions showed that insulin release from nanogels was high in pH 6.8, and low in acidic environments. Thus, pH responsive insulin loaded nanogels can be considered as a potential candidate for oral insulin therapy [71]. Interpenetrating polymeric nanogels were prepared using biocompatible gelatin macromolecules and poly (acrylamidoglycolic) acid using free radical emulsion polymerization technique.…”
Section: Microgelsmentioning
confidence: 99%
“…These were methods such as double emulsion (w/o/w), probe type sonication, and solvent evaporation ( Figure 3). PCL-PEG nanoparticles loaded with cisplatin were prepared using the double emulsion method (Karnoosh-Yamchi et al 2014). An aqueous solution of cisplatin (0.4 ml) was added and emulsified in 2 ml of dichloromethane (Karnoosh-Yamchi et al 2014).…”
Section: Drug Loadingmentioning
confidence: 99%
“…PCL-PEG nanoparticles loaded with cisplatin were prepared using the double emulsion method (Karnoosh-Yamchi et al 2014). An aqueous solution of cisplatin (0.4 ml) was added and emulsified in 2 ml of dichloromethane (Karnoosh-Yamchi et al 2014). Thus, 100 mg of the copolymer was emulsified in the mixture, using probe sonication at 10 W for 45 s. The mixture obtained (w/o emulsion) was added to an aqueous solution of sodium cholate (6 ml), and was then probe sonicated at 18 W for 1 min.…”
Section: Drug Loadingmentioning
confidence: 99%
“…It has been confirmed for instance that size is a critical parameter inducing the transverse relaxivity R 2 (Tromsdorf et al 2007) although the surface contact influences the longitudinal relaxivity R 1 (Hachani et al 2011, Tromsdorf et al 2007). Great efforts have been devoted to construct multifunctional lanthanide-based nanoprobes for multi-modality imaging (Billotey et al 2003, Corot 2006, Darrasse and Ginefri 2003, Karnoosh-Yamchi et al 2014, Lévy et al 1993, Pawelczyk et al 2009, Smirnov 2008. Some lanthanide ions with unpaired 4f electrons, like Gd 3+ ions, are generally applied as CAs for MRI.…”
Section: Properties Of Mnps For Mrimentioning
confidence: 99%